2022
DOI: 10.3389/fmicb.2022.1069694
|View full text |Cite
|
Sign up to set email alerts
|

Pectin supplement alleviates gut injury potentially through improving gut microbiota community in piglets

Abstract: As pectin is widely used as a food and feed additive due to its tremendous prebiotic potentials for gut health. Yet, the underlying mechanisms associated with its protective effect remain unclear. Twenty-four piglets (Yorkshire × Landrace, 6.77 ± 0.92 kg) were randomly divided into three groups with eight replicates per treatment: (1) Control group (CON), (2) Lipopolysaccharide-challenged group (LPS), (3) Pectin-LPS group (PECL). Piglets were administrated with LPS or saline on d14 and 21 of the experiment. Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Critically ill patients are more likely to have gastric reflux when they are lying on their back, resulting in vomiting ( 33 ). Pectin can combine well with calcium ions in the nutrient solution without changing the composition of the nutrient solution to form semi-solid, which is similar to the chyme state in which food is ground in the stomach and reduces the occurrence of reflux ( 34 , 35 ). Reducing the incidence of vomiting is more in line with the physiological characteristics of human digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients are more likely to have gastric reflux when they are lying on their back, resulting in vomiting ( 33 ). Pectin can combine well with calcium ions in the nutrient solution without changing the composition of the nutrient solution to form semi-solid, which is similar to the chyme state in which food is ground in the stomach and reduces the occurrence of reflux ( 34 , 35 ). Reducing the incidence of vomiting is more in line with the physiological characteristics of human digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Although no differences were found in the jejunum, they gradually emerged from the ileum. The improvement of intestinal immune function of newborn piglets is thought to be mediated by microorganisms ( 56 , 57 ). A study showed a similar result of a maternal soluble fiber diet increasing the plasma concentrations of anti-inflammatory factors, IL-10, in the offspring, and both sows and piglets were found to have lower plasma TNF-α levels with soluble fiber intake ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in animal models and in in vitro experiments that pectin derived from citrus plant and papaya may interact with pattern recognition receptors (PAMPs) and may thereby diminish their response to challenges with bacterial toxins 49 . Also, when consumed regularly at higher concentration, pectin may also affect intestinal barrier function [50][51][52] . Moreover, it has been suggested that pectin gel particles may bind bacterial endotoxin 53 .…”
Section: Discussionmentioning
confidence: 99%